نقد متن الحديث فى ضوء نتائج العلوم التجريبية : دراسة نظرية - Kudratovich, Shirinov Mukhiddine (al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2006)
This study deals with the issue of how to solve contradictions between the Prophetic sayings and the outcomes of the Natural Sciences, answering the following questions: (1) Is it possible that the early scholars of ×adith may have made mistakes in their classification of some ×adiths that are within the field of Natural Sciences? (2) To what extent does the Shari'ah recognize the outcomes of the Natural Sciences? (3)What are the levels of information inferred from different categories of accepted ×adiths? (4) What is the position of the so-called "The Consensually Accepted ×adiths" and ×adiths of the two authentic collections (al-ØaÍiÍayn) on the issue? (5) What are the levels of information provided by different scientific concepts? (6) What is the correct method to solve assumed contradictions between the Prophetic sayings and the outcomes of the Natural Sciences? The researcher used inductive and critical analytic methods in an attempt to produce an accurate scientific method to solve the contradictions between the various levels of information that different categories of the Prophetic sayings produce and the different levels of the outcomes of the Natural Sciences. The research has affirmed that the Shari'ah relies on the outcomes of the Natural Sciences as much as it does on the different categories of the Prophetic sayings. It also found that it is possible that the early scholars of ×adith may have made mistakes in their classification of some ×adiths that are within the field of the Natural Sciences because what they have done was IjtihÉd which is open to error and because of their limited knowledge of these things, due to the fact that the Natural Sciences of those days did not provide sufficient information. The study defined different levels of information provided by every category and concept of ×adith and the Natural Sciences, which led to wade into difficult issues such as defining what levels of information "The Consensually Accepted ×adiths" and ×adiths of al-SaÍiÍayn produce. The research reached the conclusion that none of the scientific outcomes or categories of ×adith produce certainty of the knowledge and absolute truth except for al-MutawÉtir, although the level of uncertainty differs from one to another. It also affirmed that the allegation about the total acceptance of al- SaÍiÍayn by the Ummah is inaccurate, and these ×adiths and "The Consensually Accepted ×adiths" do not produce more than a strong assumption. Finally, the research devised a method to solve assumed contradictions between the two sources of knowledge, as a solution to revolving the contradictions between two uncertain pieces of evidence. This method consists of four stages; firstly, to verify the existence of the a contradiction, secondly, to reconcile it if possible, thirdly, to give preponderance to the stronger over the weaker if the reconciliation is impossible and fourthly to impose the status quo pending further development, if both opponent parties are of equal status.